Evaluation and Optimization of Protein Extraction From E. coli by Electroporation - Haberl Meglič, Saša; Janež, Nika; Peterka, Matjaž; Flisar, Karel; Kotnik, Tadej; Miklavčič, Damijan (Frontiers in Bioengineering and Biotechnology, 2020)
Growing diversity of protein-based technologies dictates further development of bio manufacturing to lower the cost of production and maximize yields. Intracellularly expressed recombinant proteins must be extracted from production host prior to purification. Use of electroporation to obtain proteins from bacteria and yeasts has been demonstrated in several studies for different modes of operation and formats. Here we tested various protocols for protein extraction from E. coli by means of electroporation. The tested protocols were compared to established extraction methods of ultrasonication and glass-bead milling in terms of protein yields and content of impurities such as host cell DNA and endotoxins in the lysate. Protein extraction yield was maximal when exponentially growing bacteria were treated at 37 °C, regardless of the electroporation mode of operation (batch or flow). We were unable to eliminate co-extraction of host DNA and endotoxins, but with 8 x 1 ms, 5 kV/cm, 1 Hz pulses they were minimized. Yields with optimized electroporation (up to 86 g protein/kg dry weight) were inferior to those in ultrasonication (up to 144 g protein/kg dry weight) and glass-bead milling (up to 280 g protein/kg dry weight). Nevertheless, electroporation largely avoids cell lysis and disintegration with which the extract is a mix of extracted proteins with debris of the bacterial envelope and bacterial DNA, which necessitates further purification.